A Comparative Study of Enhanced Recovery after Surgery Versus Non-Enhanced Recovery after Surgery in Emergency Surgery for Duodenal Ulcer Perforation - Thapa, P.; Sharma, A.; Mahato, N. (Kathmandu University Medical Journal, 2021)
Background Enhanced recovery after surgery is a multimodal strategy, used to attenuate the loss and improve the restoration of functional capacity after surgery. Now widely used in elective surgery, the implementation of all of its components is not feasible in emergency surgery. Therefore, its tailored protocol is likely to give better outcome. Objective To investigate the feasibility and effectiveness of enhanced recovery after surgery in emergency surgery for Duodenal Ulcer Perforation. Method Hospital based study conducted at Nepalgunj Medical College, Kohalpur from September 2018 to 2020. Hundred patients underwent emergency laparotomy with Classical Graham’s Patch Repair. Fifty patients in the enhanced recovery after surgery group were managed as per the protocol and the rest were managed conventionally. Both the groups were compared in terms of length of hospital stay, functional recovery parameters and complications. Result There were 48 (96%) males and 2 (4%) females in enhanced recovery after surgery group and 45 (90%) males and 5 (10%) females in non-enhanced recovery after surgery group. The mean length of hospital stay in enhanced recovery after surgery group was 4.9 ± 0.76 days together with early functional recovery compared to 9.06 ± 2.44 days in non-enhanced recovery after surgery group (p < 0.05). Complications as per Clavien-Dindo grading were more in the non- enhanced recovery after surgery group (p=0.03). Conclusion Enhanced recovery after surgery is feasible and effective strategy resulting in early recovery, reduced hospital stay and complications in patients undergoing emergency surgery for duodenal ulcer perforation.